SALINITY OF SOILS OF INTERMOUNTAIN DEPRESSIONS IN THE DESERTS OF THE ZALTAI GOBI OF MONGOLIA - E. Pankova (Бюллетень Почвенного института им. В.В. Докучаева)
Intermountain depressions (depressions) are a characteristic feature of Zaaltai Gobi landscapes in Mongolia. There are three types of depressions, each of which is characterized by peculiarities of soil structure and specificity of soil salinity. The first type is low intermountain depressions - zones of accumulation of modern flood waters. Takyrs are formed at the bottom of depressions. The second type is the salt marshes, the formation of which is determined by the seepage of ground (ground) waters. The bottom is occupied by saline soils, sandy soils, takyrs and takyr-like soils. These are zones of modern salt accumulation. The third type is the highest absolute levels of dry depressions, filled mainly with ancient melpaleogene salt rocks, often washed away by the Saur channels. Ancient saline rocks (reddish flowers) form lithogenic solonchaks, the salinity of which is associated with the salinity of soil-forming rocks.